Importance of digitalising procurement in material acquisition for cost control at onshore fabrication projects in the oil and gas industry - Mohd Roshdi , Farrah Rina; Othman, Norhiza (International Journal of Accounting, Finance and Business, 2025)
The improvement in cost control measures throughout the procurement process, particularly regarding resource cost awareness to mitigate cost overruns, is becoming concerning. The cost control component is necessary to enhance understanding of the current and prospective function of the procurement phase in acquiring the materials in multi-billion EPC projects relative to project value. This study defines onshore fabrication as an Engineering Procurement Construction (EPC) contract and project that entails the fabrication of offshore platforms, particularly jackets and topsides, intended for the upstream industry. The issue of inadequate coordination cannot be resolved merely by distributing resources and expending funds on projects without appropriate material management planning. Consequently, the implementation of a strategic digitalization plan is essential to organise and oversee cost control measures in order to execute procurement activities and responsibilities effectively, irrespective of budgetary excesses. The objective of this research is to provide a benefit of digitalization during the procurement process for onshore fabrication projects. This research utilises data gathered from semi-structured interviews with EPC procurement experts concerning current work procedures related to the material management in EPC projects, framed within Decision Making Theory as determinants of organisational success. The data was evaluated to discover the strategic constructions and qualities, as well as to ascertain the digitalization cost control component during the procurement phase’s workflow for effective project cost management in successful EPC projects. The research indicated that successful EPC projects are associated with components of data sources about project activities such as planning and scheduling work programme during the review stage together with the prescribed fabrication cost or parameters to coordinate and mitigate cost overruns. The study's results indicated that a digitalization strategy is essential for the EPC fabricator to effectively manage EPC projects.